Enteropathogenic Escherichia coli Associated with Diarrhea in Children in Cairo, Egypt - Behiry, Iman K. (TheScientificWorldJOURNAL, 2012)
In this study we isolate and identify the Enteropathogenic Escherichia coli (EPEC) causing diarrhea in children less than five years in Cairo, Egypt, during different seasons. Children younger than five years with diarrhea, attending the Pediatric Gastroenterology Intensive Care Unit of the Cairo University Pediatric Hospital in one year period were our group of study. Our control group was age and sex matched concurrent healthy children. The identified E. coli isolates were subjected to antimicrobial disc diffusion susceptibility test and further identified for EPEC serotype by slide agglutination test, using antiserum E. coli somatic trivalent I (O111, O55, O26) according to the instructions of the manufacturer. Out of 134 patients 5.2% of them revealed EPEC in the fecal sample, while the 20 children control group showed no EPEC isolates in their samples. Our EPEC frequency showed variations from the compared results of other studies. Higher rate of EPEC (18.7%) was found in patients between 2 to 3 years, while EPEC rate was (7.5%) in patients less than 6 months old, with P < 0.05. EPEC was identified from fecal specimens as a unique pathogen or associated with other pathogens in acute and chronic diarrhea in children. EPEC were detected in all seasons except in winter, and was predominant in summer season. Four (57%) EPEC isolates were resistant to ampicillin, ticarcillin, and cotrimoxazole, and (14.3%) to the third generation cephalosporins.